2021
DOI: 10.1038/s41598-021-90638-0
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity CRP may be a marker of HDL dysfunction and remodeling in patients with acute coronary syndrome

Abstract: In patients with coronary artery disease (CAD), further increasing the level of high-density lipoprotein (HDL) cholesterol (HDL-C) as an add-on to statins cannot reduce cardiovascular risk. And it has been reported that HDL functional metric—cholesterol efflux capacity (CEC) may be a better predictor of CAD risk than HDL-C. CEC measurement is time-consuming and not applicable in clinical settings. Thus, it is meaningful to explore an easily acquired index for evaluating CEC. Thirty-six CAD patients and sixty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Notably, elevated hs-CRP with low HDL-C level is significantly linked to an increased incidence of all-cause death in patients who received PCI. Moreover, hs-CRP is found to be inversely associated with the RCT of HDL and the association between hs-CRP and coronary artery calcification score could be modified by HDL-C [ 7 , 104 ]. Therefore, hs-CRP to HDL-C ratio (CHR) is explored and has been discovered to be an independent predictor of CAD presence (adjusted OR, 1.178; 95% CI, 1.016–1.366; P = 0.03) with a specificity of 86.7%, Yoden index of 0.264 and AUC of 0.662 (95% CI, 0.606–0.719; P < 0.001) [ 91 ].…”
Section: Hdl-cholesterol–related Inflammatory Parameters In Coronary ...mentioning
confidence: 99%
“…Notably, elevated hs-CRP with low HDL-C level is significantly linked to an increased incidence of all-cause death in patients who received PCI. Moreover, hs-CRP is found to be inversely associated with the RCT of HDL and the association between hs-CRP and coronary artery calcification score could be modified by HDL-C [ 7 , 104 ]. Therefore, hs-CRP to HDL-C ratio (CHR) is explored and has been discovered to be an independent predictor of CAD presence (adjusted OR, 1.178; 95% CI, 1.016–1.366; P = 0.03) with a specificity of 86.7%, Yoden index of 0.264 and AUC of 0.662 (95% CI, 0.606–0.719; P < 0.001) [ 91 ].…”
Section: Hdl-cholesterol–related Inflammatory Parameters In Coronary ...mentioning
confidence: 99%
“…Some studies have suggested, based on the observation that individuals with higher levels of large HDL particles have a lower risk of CVD, that larger HDL particles are more protective against CVD than smaller HDL particles [ 28 , 29 ]. On the contrary, other studies showed that small, dense HDL particles may actually be more protective against CVD than larger particles [ 30 , 31 , 32 ]. This controversy suggests that the relationship between HDL particle size and CVD risk is complex and may depend on other factors such as the presence of other lipid abnormalities or genetic factors [ 33 ].…”
Section: Discussionmentioning
confidence: 94%
“…According to a study, HDL cholesterol levels might not be a good predictor of MACE in CAD patients, i.e., serum levels of HDL cholesterol might not accurately reflect the true cholesterol efflux capacity of HDL. The researchers further found that the assessment of cholesterol efflux capacity provided the most reliable reflection of HDL function and cardiovascular risk and speculated that the disjunction between serum HDL concentration and its functional capacity might be caused by inflammation-induced remodeling of HDL subclass [ 34 ]. In another study, the cholesterol efflux capacity was reduced in ACS patients and remained low during the 3-month follow-up period when compared to stable CAD patients, independent of changes in HDL cholesterol levels or Apo lipoprotein A-I.…”
Section: Discussionmentioning
confidence: 99%